Ring Vortex Dynamics Following Jet Formation of a Bubble Expanding and Collapsing Close to a Flat Solid Boundary Visualized via Dye Advection in the Framework of OpenFOAM - Max Koch; Werner Lauterborn; Christiane Lechner; Robert Mettin (Fluids, 2023)
A bubble expanding and collapsing near a solid boundary develops a liquid jet toward the boundary. The jet leaves a torus bubble and induces vortices in the liquid that persist long after the bubble oscillations have ceased. The vortices are studied numerically in axial symmetry and compared to experiments in the literature. The flow field is visualized with different methods: vorticity with superimposed flow-direction arrows for maps at a time instant and colored-liquid-layer flow-field maps (dye advection) for following the complete long-term fluid flow up to a chosen time since bubble generation. Bubbles with equal energy—maximum radius in a free liquid <semantics><msubsup>Rmax∞</msubsup></semantics>= 500 µm—are studied for different distances <semantics>Dinit</semantics> from the solid boundary. The interval of normalized distances <semantics>D*</semantics> = <semantics>Dinit</semantics>/<semantics><msubsup>Rmax∞</msubsup></semantics> from 0.4 to 1.8 is covered. Two types of vortices were reported in experiments, one moving toward the solid boundary and one moving away from it. This finding is reproduced numerically with higher resolution of the flow field and in more detail. The higher detail reveals that the two types of vortices have different rotation directions and coexist with individually varying vorticity amplitude throughout the interval studied. In a quite narrow part of the interval, the two types change their strength and extent with the result of a reversal of the dominating rotational direction of the fluid flow. Thereby, the experimentally found transition interval could be reproduced and refined. It is interesting to note that in the vortex transition interval, the erosion of a solid surface is strongly augmented.